2009
DOI: 10.1007/s12011-009-8473-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Peritubular Tissue of Rat Testis after Cadmium Treatment

Abstract: The present study demonstrates histological and immunohistochemical changes in the peritubular testicular tissue of rat testis after application of cadmium chloride. After 5-day cadmium exposure, advanced deterioration of the boundary testicular tissue, mainly oedema, disarrangement of collagen fibres and peritubular cells, dilatation and thrombosis of blood vessels were observed. Changes in the boundary tissue were accompanied with desquamation of the germinal epithelium. Immunohistochemically, positive react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…Cd inhibit the assembly of Sertoli cells TJ-permeability barrier and decreased synthesis and/or expression of proteins by promoting protein redistribution at the Sertoli-Sertoli cell interface. Tight junction proteins occludin, N-cadherin and vimentin were partially or completely disrupted by a cadmium injection (Janecki et al, 1992;Hew et al, 1993a;Bekheet, 2010;Marettová et al, 2010). As the time after Cd exposure increased, the lesion within a stage occured with increasing severity, and later stages of the cycle of the seminiferous epithelium were also affected.…”
Section: Effect Of CD On Blood-testis Barriermentioning
confidence: 99%
See 3 more Smart Citations
“…Cd inhibit the assembly of Sertoli cells TJ-permeability barrier and decreased synthesis and/or expression of proteins by promoting protein redistribution at the Sertoli-Sertoli cell interface. Tight junction proteins occludin, N-cadherin and vimentin were partially or completely disrupted by a cadmium injection (Janecki et al, 1992;Hew et al, 1993a;Bekheet, 2010;Marettová et al, 2010). As the time after Cd exposure increased, the lesion within a stage occured with increasing severity, and later stages of the cycle of the seminiferous epithelium were also affected.…”
Section: Effect Of CD On Blood-testis Barriermentioning
confidence: 99%
“…All testicular germ cell populations can by affected by Cd. This includes a decrease in number of spermatogonia and spermatocytes, aberrant morphology in all developing stages, release of immature cells into the lumen (Aoyagi et al, 2002;Zhou et al, 2004;Marettová et al, 2010) and failure in spermiation (Hew et al, 1993b). Elongated and round spermatids, as well as spermatocytes were found in the tubule lumen in >98% of tubules (Mruk and Cheng, 2011).…”
Section: Effect Of CD On Germinal Epitheliummentioning
confidence: 99%
See 2 more Smart Citations
“…99 It is possible that Cd may be affecting osteoblasts' ability to produce collagen type I, a structural protein whose role it is to assemble a scaffold for bone mineralization. In the testis, Cd was found to disrupt the organization of collagen fibrils residing within the tunica propria (it is not known if type I and/or type IV collagen was affected), 100 indicating that Cd targets a critical understructure on which all cells of the seminiferous epithelium reside. Other studies relating to the skeleton have reported the harmful effects of environmental toxicants to be also mediated by AhR.…”
Section: Environmental Toxicants Bone and Male Reproductive Functionmentioning
confidence: 99%